2011
DOI: 10.1177/0267659111419035
|View full text |Cite
|
Sign up to set email alerts
|

Are minimized perfusion circuits the better heart lung machines? Final results of a prospective randomized multicentre study

Abstract: These results confirm both the safety and efficacy of the ROCsafeRX MPC for a large variety of cardiac patients. Minimized perfusion circuits should, therefore, play a greater role in daily practice so that as many patients as possible can benefit from their advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 23 publications
3
43
3
1
Order By: Relevance
“…In contrast, Anastasiadis et al reported in their large meta‐analysis of 24 studies and c. 2800 patients that MiECC reduced the occurrence of POAF from 27.6% to 19.2% 20 . Correspondingly, of the four randomized trials comparing MiECC and CECC, two reported that MiECC was associated with 33%‐38% reduction in the development of POAF 21,22 . In the study by El‐Essawi, the incidence of POAF reduced from 24.2% to 16.3%, and in the study by Anastasiadis from 53.3% to 33.3%.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, Anastasiadis et al reported in their large meta‐analysis of 24 studies and c. 2800 patients that MiECC reduced the occurrence of POAF from 27.6% to 19.2% 20 . Correspondingly, of the four randomized trials comparing MiECC and CECC, two reported that MiECC was associated with 33%‐38% reduction in the development of POAF 21,22 . In the study by El‐Essawi, the incidence of POAF reduced from 24.2% to 16.3%, and in the study by Anastasiadis from 53.3% to 33.3%.…”
Section: Discussionmentioning
confidence: 88%
“…In our study, as well as in all the aforementioned studies patients undergoing CABG with no additional surgery were studied. In spite of this, the incidence of POAF in the reference group (CECC) has ranged considerably, from 19% to 53% 17,21‐24 . This most probably depicts different definition of POAF used in these trials.…”
Section: Discussionmentioning
confidence: 96%
“…In our study we found earlier rise of the CRP and procalcitonin levels as well as leukocyte count in the 'mini-CPB' group than in the control group by approximately 24 h, with a gradual decrease thereafter in both groups. Higher average levels of inflammatory markers in the 'mini-CPB' group This is related to higher HGB and HCT levels after the 'mini-CPB' procedure is conducted [4,5]. This significantly smaller decrease in HCT level is caused by minimal haemodilution.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, there are only three with more than 100 patients randomized in each arm [9][10][11]. (Table 1) is a comparison of these three larger randomized trials with at least 100 patients comparing M-CPB to C-CPB.…”
Section: Common Features To M-cpbmentioning
confidence: 99%
“…(Table 1) is a comparison of these three larger randomized trials with at least 100 patients comparing M-CPB to C-CPB. Two of the studies [9,10] demonstrate a clear benefit with respect to bleeding and transfusion either in the OR, the first 24 hours, or in actual reoperations for bleeding. After isolated CABG with conventional CPB (C-CPB) it has been well demonstrated in large studies that perioperative red blood cell (RBC) transfusion is an important factor in postoperative mortality, infection, ischemic postoperative morbidity, hospital stay, and hospital costs [12].…”
Section: Common Features To M-cpbmentioning
confidence: 99%